Manajemen Pembelajaran Nahwu Sharaf Menggunakan Metode Tamyiz Pada Masa Pandemi Covid 19 - Azman Arif; Mahmud Mannan; Abu Darim (Perkumpulan Dosen Tarbiyah Islam Indonesia, 2022)
This article's purpose was to determine the process of planning, organization, implementation, obstacles, and completion of the Nahwu Sharaf learning management at LKP Al-Azhar Pare, Kediri that used the Tamyiz method during the Covid 19 pandemic. This research was a type of qualitative research with a case study approach. The data obtained from this study were sourced from primary data through observation, interviews and secondary data indirectly. The research technique used is observation, interviews, and documentation. The results showed that the planning process for Nahwu Sharaf at LKP Al-Azhar Pare, the institution only had a syllabus not lesson plans because it focused on the target for each period. In the process of organizing, the director and the manager have done a clear division of tasks among all coordinators, teachers, and the person in charge of the class. The process of implementing online learning for the new period began in every first and offline every tenth, these classes can be accessed in their own class. While the obstacles in this study were due to network instability, task force control which took a lot of time, many participants were late during zoom meetings, and different understanding of children based on their backgrounds. The solution is to give additional online or offline facilities to students who can ask questions they are not understood. The most important of this method is to multiply practice and repeat personally.